Estudo comparativo de aguardentes moçambicanas e brasileiras - Tábua, Manuel Carlos Minez (2018)
In Mozambique, the agribusiness involving the production of distilled spirits has been gaining ground among small producers, influencing the local economy and the country, and generating jobs and profits. The distilled spirit is an alcoholic beverage obtained from fermented and distilled sugarcane must or other raw materials (fruits or tubers), with an alcoholic strength between 38% and 54% v/v at 20 °C. In Brazil, the chemical composition and quality requirements are regulated by the Ministry of Agriculture, Livestock and Food Supply (MAPA). The objectives of this work were to analyze the physicochemical quality of spirits produced in the Central and Northern regions of Mozambique, according to the Identity and Quality Standards (PIQ's) established by Brazilian legislation and to compare them with Brazilian samples, randomly collected from different producers in Minas Gerais, Brazil. The Mozambique samples were collected in the regions of Xinavane, Manhiça, Chokwe, Beira, Mafambisse, Massingae and Chimoio de Moçambique. All the samples were sent to the Laboratory of Physical and Chemical Analysis of Spirits of the Department of Chemistry of the Federal University of Lavras (LAFQA/DQI). These parameters were evaluated: alcohol concentration, volatile acidity, higher alcohols, aldehydes, esters, methanol, furfural, volatile compounds, glycerol and trace elements. The higher alcohols were characterized and quantified by gas chromatography, and the volatile compounds by gas chromatography coupled to a mass spectrometer (GC-MS) at the Center for Chemical Analysis and Prospecting (CAPQ/DQI/UFLA). The solid phase microextraction of the headspace (SPME) was used for the identification of the volatile compounds. The concentrations of the quantified components in the Mozambican spirits produced from different raw materials (cereals, sugar cane and fruits) and in the Brazilian spirits varied greatly. Regarding the standards required by the Brazilian legislation for spirits/cachaças, most Mozambican samples were found to be outside the maximum limits established for alcohol concentration, volatile acidity, furfural, and methanol, whereas Brazilian spirits analyzed in the present study were within the limits of the Identity and Quality Standards, as they are carefully controlled by the Ministry of Livestock, Agriculture and Supply in Brazil. Low concentrations of glycerol were found in the samples studied. Contamination of the Mozambican samples by metals such as copper (ND at 34.83 mg L-1), lead (600 to 3660 μg L-1), zinc (ND at 23.01 mg L-1) , and iron (ND at 0.04 mg L-1) was found. The presence of cadmium and chromium was not detected in any of the samples. Of the results obtained, 35 volatile compounds were identified in Mozambican spirits, of which 19 were esters, which contribute to the sensorial characteristics of the beverage. The results found for the parameters were adequate for the purpose of the research, which was to stimulate the producers to improve the conditions of production and to recognize the risks involved in producing a high quality brand of spirits.